Psychometric construction and analysis of social interaction competence in preschool context scale - Rangel C., Patricia (2016)
The main objective of this work is the construction and psychometric analysis of a test to evaluate Children's Social Interaction Competence between 3 to 6 years old in pre-school context. The scale construction is based on the Kelly, J. theory, about social interaction in childhood (1987). The sample consists of 400 preschool children from different socioeconomic levels, in Lima-Peru. The factor analysis shows three factors: Social interaction initiative, Ability for social interaction with peers and Ability to social interaction with teacher. The test shows construct and content validity, its reliability is 0.950, differences by age and the corresponding table of rates is presented.